Comparison of clinical characteristics and outcome of carbapenem sensitive and carbapenem resistant Klebsiella Species infection from a Tertiary-Care-Hospital, Karachi, Pakistan - Farooq, Muhammad Kashif; Babar, Zaheer Udin; Dodani, Sunil Kumar; Muhammad Hassan; Naseem, Asma (Infectious Diseases Journal of Pakistan, 2024)
Background: The prevalence of carbapenem-resistant (CR) Klebsiella species (KS) exceeds 60% in South Asia, leading to high morbidity and mortality. Data on KS clinical aspects from Pakistan is limited. This study aimed to examine the clinical characteristics, outcomes, and mortality risk factors associated with KS-infections. Material and Methods: A prospective study conducted between September 2022 and March 2023 compared patients with carbapenem-resistant KS (CR-KS) and carbapenem-susceptible KS (CS-KS) in terms of demographics, clinical features, Charlson comorbidity index, source of infection, previous hospitalization, source control, and receipt of appropriate empirical antibiotics. Outcomes were recorded as admission status, discharge, or death at day 14. Results: A study of 217 patients with a median age of 48 years found that 52% had a history of prior hospitalization, and 47.5% presented with bacteremia. Carbapenem-resistant KS (CRKS) was present in 58.9% of patients. CR-KS infection was significantly linked to recent hospitalization (p=0.01), fever (p=0.01), altered mental status (p=0.002), ICU admission (p=0.003), mechanical ventilation (p= 0.02), and pneumonia (p=0.004). CR-KS had poor bacterial clearance and a low rate of appropriate empirical antibiotic use (3.2%). At day 14, the all-cause mortality rate was 29%, with significantly higher mortality in CRKS patients, as shown by the survival curve. Multivariate analysis indicated that CR-KS patients did not receive appropriate empirical antibiotics. Conclusion: The study revealed a high prevalence of CR-KS infections associated with significant morbidity and mortality. Patients with CRKS infection did not receive appropriate empirical antibiotics. Timely availability of antibiogram with good infection control practices are critical in preventing mortality and spread this highly pathogenic organism. Keywords: Carbapenem resistant, Klebsiella, Antimicrobial resistance